A critical introduction to skepticism - Hazlett, Allan (Bloomsbury critical introductions to contemporary epistemology., 2014)
"Skepticism remains a central and defining issue in epistemology, and in the wider tradition of Western philosophy. To better understand the contemporary position of this important philosophical subject, Allan Hazlett introduces a range of topics, including:[bullet] Ancient skepticism[bullet] skeptical arguments in the work of Hume and Descartes[bullet] Cartesian skepticism in contemporary epistemology[bullet] anti-skeptical strategies, including Mooreanism, nonclosure, and contextualism[bullet] additional varieties of skepticism[bullet] the practical consequences of Cartesian skepticismPresenting a comprehensive survey of the key problems, arguments, and theories, together with additional readings, A Critical Introduction to Skepticism is an ideal guide for students and scholars looking to understand how skepticism is shaping epistemology today"--